Spatial Justice: Geographical Conceptualization in the Context of War in Ukraine - Gukalova, I. V.; Maruniak, Eu. O.; Lisovskyi, S. A.; Mozghovyi, A. A.; Poklyatskyi, S. A.; Gormiz, O. V. (Ukrainian Geographical Journal, 2024)
As a scientific category, spatial justice requires a detailed and in-depth theoretical and methodological study, as well as empirical evaluation. Since representatives of different fields of knowledge offer their own definitions of spatial justice, it is impossible to have a systematic view of it, nor to place accents that are important for geographers. The purpose of the study is to analyze and summarize approaches to the definition of “spatial justice”, to outline its main dimensions, and to clarify, through an online expert survey of geographers, the essence of the category and the focus of its study in the context of the military situation in Ukraine. The analysis of the literature and the results of an online survey of geographers on the nature of spatial justice in Ukraine revealed that justice is based on the principle of equal opportunities, which is worth striving for, given the objective geographical inequalities in living conditions, access to services, mobility levels, etc. Even though the category of “spatial justice” has been defined by geographers in the past, it is not yet clear what its main dimensions are or what its focus should be. Although the field of spatial justice is most developed in Western countries, its implementation in war and post-war conditions in Ukraine is particularly necessary, especially given the injustice of war, which is exacerbated by its consequences. According to the majority of respondents, spatial justice can be interpreted as the achievement of a state in which the economic life of a given territory is subordinated to, or at least does not contradict, the interests of the local community, creating benefits and opportunities to meet production, cultural, and other needs. In times of war, it is also a fair democratic process of sharing benefits and risks between territories. The definitions chosen by the majority of respondents can serve as a basis for further development of theoretical, methodological, and practical tools to build a platform for implementing the principles of spatial justice at different territorial levels.
Keywords: spatial justice; geographical inequality; survey; living conditions; Russian-Ukrainian war